Pemanfaatan Google Site dalam Pembelajaran untuk Meningkatkan Motivasi Belajar Siswa Sekolah Menengah Kejuruan (SMK) - Mahalasari (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2022)
This research was conducted to analyze the need for learning media that can support face-to-face and distance learning with utilization of google site as learning media to increase the learning motivation of vocational high school students. This research is expected to provide new input and to be one of the successful solutions in the learning process. Learning media is an intermediary tool used by educators in delivering learning to students. Learning using one of the media in the form of an application or website is one of the innovations in the world of education to answer the challenge of the availability of varied learning resources. One of the right types of media is to use the google site in making teaching materials. This research is a systematic literature review (SLR) research. Data collection is done by documenting and reviewing artivles or journals related to the google site. Based on the results of the research that has been carried, it is explained that the google site can be used as learning medium to increase the learning motivation of SMK students.